PEDAGOGICAL OPPORTUNITIES FOR ORIENTING AND PREPARING STUDENTS FOR SCIENTIFIC AND PROFESSIONAL ACTIVITIES - Jumayev Abdilkhakim Turdiyevich (Bright Mind Publishing, 2025)
This article provides guidelines and suggestions on the didactic possibilities and stages of acmeology for directing and preparing students for scientific and professional activities.
Keywords: Direction, quality, acmeology, master, excellence, productivity, professionalism, promotion.